1997
DOI: 10.1557/s0883769400033972
|View full text |Cite
|
Sign up to set email alerts
|

Sputter-Deposited Low-Emissivity Coatings on Glass

Abstract: IntroductionLow-emissivity (low-E) and solarcontrol coatings increase the energy efficiency of clear float soda-lime-silicate glass for architectural and automotive window applications. At the same time, coated glass largely maintains its neutral color and high visible transmittance. Two major classes of coated products are currently available for the architectural market: The more durable chemicalvapor-deposition (CVD) coatings are deposited on float glass as it is formed. The vacuum deposited low-E coatings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…1,2 Typical low-e coating structures are transparent dielectric/Ag/dielectric multilayer films. 3 Silver is widely used as the reflectance layer because of its good electrical and optical properties [4][5][6] and has different properties depending on whether the growth is 2-dimensional (2-D) or 3dimensional (3-D). It has been reported that the silver films grew via a 3-D Volmer-Weber mechanism 7 due to poor wettability on metal oxides and were prone to agglomeration at a relatively low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Typical low-e coating structures are transparent dielectric/Ag/dielectric multilayer films. 3 Silver is widely used as the reflectance layer because of its good electrical and optical properties [4][5][6] and has different properties depending on whether the growth is 2-dimensional (2-D) or 3dimensional (3-D). It has been reported that the silver films grew via a 3-D Volmer-Weber mechanism 7 due to poor wettability on metal oxides and were prone to agglomeration at a relatively low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…There is a report that silver film does not show significant conductivity until its thickness exceeds few nm, e.g. >30 nm, when it becomes continuous and its resistivity decreases with thickness [16][17][18]. However, this thickness of silver film depends on the deposition process and the substrate on which it is deposited [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…It can be used either as a top coat for mechanical protection or as an intermediate refractive index layer for optimization of the optical performance . Currently, the deposition of Low‐E coatings is mainly performed by magnetron sputtering, a class of physical vapor deposition techniques. In particular, reactive magnetron sputtering is easy to scale‐up, offers low thermal load on the substrate, can be operated with lower environmental impact than chemical vapor deposition, and allows excellent process control, albeit at the expanse of relatively low deposition rates .…”
Section: Introductionmentioning
confidence: 99%